Pengelolaan Arsip Dalam Mendukung Pelayanan Informasi Pada Bagian Tata Usaha di Dinas Sosial Kabupaten Ponorogo - Sri Ardiana; Bambang Suratman (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Archives are very important for an organization because as a source of organizational information relating to the development and operational activities of a business or government organization. More and more organizational work will also increase the number of records produced. From time to time the number of records will increase, requiring management. Records management is an important aspect in an organization, both business organizations and good government so that the information to be sought can be found quickly and accurately. Managing archives manually that has been done so far, has several weaknesses, including: requiring large space and storage, the risk of damage to the archive due to disaster, requires a lot of employees and a long search time. This study aims to determine the records management procedure which includes receiving incoming and outgoing mail, archiving, rediscovering records, and maintaining records. This research is a qualitative descriptive study. The subjects of this study were 3 administrative staff from Ponorogo Regency Social Service. Data analysis refers to the Miles and Huberman model using source triangulation and research instruments in the form of interviews and documentation. Based on the results of a study entitled "Management of Archives in Supporting Information Services in the Administration Section at the Social Service Agency of Ponorogo" that records management in supporting information services has been running well because the management system is in accordance with the filing procedures.